PELATIHAN TATA KELOLA ADMINISTRASI DAN KEUANGAN KOPERASI MERAH PUTIH DESA TALABIU - Rimawan, Muhammad; Puji Muniary; Alwi, Alwi; Hanifah Muthiah; Ainun Fitrani (Nusantara Hasana Journal, 2025)
The development of digital technology has presented new opportunities and challenges for cooperative management, particularly for community-based cooperatives oriented towards the people’s economy. The Red and White Cooperative is required to adapt to digital-based administrative and operational management systems to improve efficiency, accountability, and institutional transparency. However, many Red and White Cooperatives still experience limitations in technological mastery, low digital literacy among administrators, and weak systematic managerial systems. To address these issues, this Community Service activity was designed in the form of training aimed at improving the capacity of cooperative administrators in managing digital administration and implementing adaptive operational management strategies. The implementation method included identifying the needs of cooperative partners, developing contextual training modules, conducting online training, and evaluating and following up. Training materials covered digitalization of financial records, institutional document management, developing SOPs, and using cooperative management applications. The results of the activity showed an increase in participants’ understanding of digital administration, as well as improved managerial skills in developing work plans, SOPs, and cooperative performance indicators. In addition, the online training method was considered effective by participants because it was flexible and able to reach cooperatives in remote areas.